Enhancement of epidermal growth factor receptor antibody tumor immunotherapy by glutaminyl cyclase inhibition to interfere with CD47/signal regulatory protein alpha interactions. Issue 8 (18th June 2021) - Baumann, Niklas; Rösner, Thies; Jansen, J. H. Marco; Chan, Chilam; Marie Eichholz, Klara; Klausz, Katja; Winterberg, Dorothee; Müller, Kristina; Humpe, Andreas; Burger, Renate; Peipp, Matthias; Schewe, Denis M.; et al.
Abstract: Integrin associated protein (CD47) is an important target in immunotherapy, as it is expressed as a "don't eat me" signal on many tumor cells. Interference with its counter molecule signal regulatory protein alpha (SIRPα), expressed on myeloid cells, can be achieved with blocking Abs, but also by inhibiting the enzyme glutaminyl cyclase (QC) with small molecules. Glutaminyl cyclase inhibition reduces N‐terminal pyro‐glutamate formation of CD47 at the SIRPα binding site. Here, we investigated the impact of QC inhibition on myeloid effector cell‐mediated tumor cell killing by epidermal growth factor receptor (EGFR) Abs and the influence of Ab isotypes. SEN177 is a QC inhibitor and did not interfere with EGFR Ab‐mediated direct growth inhibition, complement‐dependent cytotoxicity, or Ab‐dependent cell‐mediated cytotoxicity (ADCC) by mononuclear cells. However, binding of a human soluble SIRPα‐Fc fusion protein to SEN177 treated cancer cells was significantly reduced in a dose‐dependent manner, suggesting that pyro‐glutamate formation of CD47 was affected. Glutaminyl cyclase inhibition in tumor cells translated into enhanced Ab‐dependent cellular phagocytosis by macrophages and enhanced ADCC by polymorphonuclear neutrophilic granulocytes. Polymorphonuclear neutrophilic granulocyte‐mediated ADCC was significantly more effective with EGFR Abs of human IgG2 or IgA2 isotypes than with IgG1 Abs, proposing that the selection of Ab isotypes could critically affect the efficacy of Ab therapy in the presence of QC inhibition. Importantly, QC inhibition also enhanced the therapeutic efficacy of EGFR Abs in vivo. Together, these results suggest a novel approach to specifically enhance myeloid effector cell‐mediated efficacy of EGFR Abs by orally applicable small molecule QC inhibitors. Abstract : Inhibition of CD47/signal regulatory protein alpha (SIRPα) interactions is of great interest in cancer immunotherapy. In this manuscript, we investigated the impact of glutaminyl cyclase inhibition by small molecules to interfere with CD47/SIRPa interactions in epidermal growth factor receptor Ab‐mediated tumor immunotherapy in vitro and in vivo.